2014
DOI: 10.1002/art.38731
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Associated With Systemic Lupus Erythematosus in France Assessed by Multiple‐Cause‐of‐Death Analysis

Abstract: Objective. To assess the mortality profile of systemic lupus erythematosus (SLE) patients in France using multiple-cause-of-death analysis.Methods. Data were collected between 2000 and 2009 in the French Epidemiological Center for the Medical Causes of Death database, and death certificates issued upon the death of an adult for whom SLE was an underlying cause of death (UCD) or a nonunderlying cause of death (NUCD) were evaluated using multiple-cause-of-death analysis. Sex, age, sex ratio, standardized mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
5
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 33 publications
2
114
5
6
Order By: Relevance
“…The discrepancy could be partly attributed to different age of patients among the groups, as patients included in most of the other studies were much older than ours. To support this notion, it has been reported that elder patients were more often died with SLE as the non-underlying cause instead of the underlying cause [9,12]. In addition, patients in the Asia-Pacific region have been identified to possess more severe manifestations than Caucasians [13], which may also contribute to the high incidence of SLE related deaths in this group.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy could be partly attributed to different age of patients among the groups, as patients included in most of the other studies were much older than ours. To support this notion, it has been reported that elder patients were more often died with SLE as the non-underlying cause instead of the underlying cause [9,12]. In addition, patients in the Asia-Pacific region have been identified to possess more severe manifestations than Caucasians [13], which may also contribute to the high incidence of SLE related deaths in this group.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most severe manifestations of SLE is lupus nephritis (LN), which is a major cause of substantial morbidity and mortality [3, 4]. Due to the heterogeneous presentation of SLE patients and their unpredictable disease course, it is essential to explore novel biomarkers that will contribute to better diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Infection is a major contributor to morbidity and mortality in systemic lupus erythematosus (SLE); infection-related hospitalisation rates range from 10% to 35% [1][2][3][4] and mortality rates range from 29% to 53%. 5 6 The disease itself and most treatment strategies are immunosuppressive, rendering patients with SLE more susceptible to severe infection with common organisms and opportunistic pathogens.…”
Section: Introductionmentioning
confidence: 99%